Exploring the relationship between Ln leaching and Ln–O binding energy in monazite (Nd, Sm, Eu). Issue 1 (6th September 2021) - Zhao, Xiaofeng; Li, Yuxiang; Teng, Yuancheng; Liu, Hang; Zheng, Xiayu; He, Hongni; Wang, Shanlin; Ahuja, Rajeev
Abstract: Understanding the chemical durability of waste forms is important for the long‐term deep geological disposal of actinides. However, in‐depth investigations on the leaching mechanism of monazite ceramic waste forms remain to be poorly understand. Inspired by the degradation process of Ce‐monazite controlled by the fracture of Ce–O bond of (010) surface under the action of permeable water molecules, the relationship between Ln leaching and Ln–O binding energy in LnPO4 (Ln = Nd, Sm, Eu) monazites is investigated by combining dissolution experiments and first‐principles calculations. The dissolution experiments are performed in 0.001 mol/L HCl solutions at 363 K. Before and after leaching, the phase compositions of specimens are carefully investigated by refined XRD and GIXRD, and the results confirm that the dissolved phases in contact with the leachate are LnPO4  monazite. Some specific issues are discussed in detail by first‐principles calculations, such as the bond length, charge transfer, electron localization function, and chemical bond properties. Moreover, the boundary conditions of crystal‐growing of LnPO4  monazite are investigated to define the chemical potential that is used to calculate the defect formation energy ( E f ) of Ln vacancy in (010) surface. Importantly, the E f results show the difficulty order of forming a vacancy defect of Ln on (010) surface is Eu > Sm > Nd, which is consistent with the leaching stability of Ln in LnPO4 (Ln = Nd, Sm, Eu) monazite. Abstract : The relationship between Ln leaching stability and Ln‐O binding energy.